Recurrent microblazar activity in Cygnus X-1? - Romero, Gustavo Esteban (2002)
Recurrent flaring events at X- and soft gamma-ray energies have been recently reported for the galactic black hole candidate Cygnus X-1. The observed fluxes during these transient outbursts are far higher than what is observed in ``normal´´ episodes. Here we suggest that the origin of this radiation is non-thermal and produced by inverse Compton interactions between relativistic electrons in the jet and external photon fields, with a dominant contribution from the companion star field. The recurrent and relatively rapid variability could be explained by the precession of the jet, which results in a variable Doppler amplification.